Glucagon in metabolic disease: a mini-review of emerging multi-organ roles beyond glycemic control - Lee, Seung Hee; Park, Hyeon Young; Yun, Ji Ho; Do, Eun Kyoung (Frontiers in Endocrinology, 2025)
Glucagon, once seen as an insulin counter-regulatory hormone, is now recognized as a key regulator of systemic energy balance, with expanding relevance across a spectrum of cardiometabolic diseases. While its traditional roles in liver glucose regulation are well established, new evidence highlights glucagon’s involvement in amino acid metabolism, fat oxidation, appetite control, heat production, and cardiovascular health. Nonetheless, the broader effects of glucagon imbalance, especially in cases of α-cell overactivity and glucagon resistance, are still not fully understood in chronic conditions like type 2 diabetes mellitus (T2DM), non-alcoholic fatty liver disease (NAFLD), chronic kidney disease (CKD), obesity, and hypertension. This mini-review consolidates current knowledge of glucagon signaling, highlighting its regulatory mechanisms, multi-organ metabolic functions, and emerging therapeutic approaches. We suggest that long-term changes in glucagon secretion could be an upstream factor driving diabetic complications affecting the liver, kidney, and cardiovascular system. By incorporating recent discoveries, we aim to establish a conceptual basis for future translational research on glucagon’s systemic effects within the framework of diabetic cardiometabolic dysfunction.